Life on Mars - The Complete Series Episode 1-17 - Fleder, Gary; Katleman, Michael; Pressman, Michael; Prinzi, Frank; DiBona, Craig; O'Mara, Jason; Imperioli, Michael; Mol, Gretchen (Twentieth Century Fox, 2010)
For New York Detective Sam Tyler (Jason O'Mara), time is relative. Very relative. While pursuing a serial killer in 2008, he is hit by a car. The next thing he knows, it's 1973. Clashing with an old-school boss (Harvey Keitel, Pulp Fiction, Reservoir Dogs) , a crass nemesis (Michael Imperioli) and the unsophisticated police procedures of the bellbottom era, Sam also finds himself in love with two co-workers (Gretchen Mol and Lisa Bonet) from two different eras. Follow the complete storyline from beginning to end in this one action-packed season that delivers brilliant writing, a first-rate cast and wall-to-wall hit songs. [Cover]
Keywords: DVD-Video